2020
DOI: 10.1186/s12903-020-1005-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of disinfection and sterilization on the dimensional changes and mechanical properties of 3D printed surgical guides for implant therapy – pilot study

Abstract: Background: The purpose of this research was to investigate the effects of disinfection and three different sterilization methods on the dimensional changes and mechanical properties of three-dimensional (3D) printed surgical guide for implant therapy. The objective was to assess the effects of sterilization procedures in 3D printed drill guide templates with destructive and non-destructive material testing. Methods: Fifteen identical drill guide templates were produced using a 3D printer. The surgical guides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 18 publications
(39 reference statements)
7
56
1
Order By: Relevance
“…In hospitals with point-of-care manufacturing, the most widely used sterilization method is steam sterilization, in which sterilization occurs in an enclosed space (autoclave), at high pressure with the help of saturated steam [35]. Several articles can be found related to the accuracy evaluation in computer-guided surgeries [36,37], yet very few of them fully describe the effects of sterilization.…”
Section: Discussionmentioning
confidence: 99%
“…In hospitals with point-of-care manufacturing, the most widely used sterilization method is steam sterilization, in which sterilization occurs in an enclosed space (autoclave), at high pressure with the help of saturated steam [35]. Several articles can be found related to the accuracy evaluation in computer-guided surgeries [36,37], yet very few of them fully describe the effects of sterilization.…”
Section: Discussionmentioning
confidence: 99%
“…(26) The surgical guide was then autoclaved at+1bar pressure and 121 o C for 20 minutes as accuracy of surgical guides is not affected when sterilized under such conditions. (27) It was then seated in place and stabilized against the upper denture. (28) Fixation of the guide then took place by the help of the anchor pins for guide stabilization during surgical procedures to minimize implant deviation.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional sterilization techniques include exposure to gamma-irradiation, ethylene oxide gas, UV irradiation, ethanol washing, and autoclaving [ 143 ]. A recent study investigated the efficacy of sterilization techniques, including plasma irradiation and autoclave steam sterilization (121°C and 134°C), for surgical guides and implants [ 144 ]. It was concluded that both plasma irradiation and autoclave steam sterilization are suitable sterilization methods, and that high temperature steam sterilization caused no significant deformation of 3D printed implants.…”
Section: Future Perspectives and Challengesmentioning
confidence: 99%